1996
DOI: 10.1016/s0092-8674(00)80984-8
|View full text |Cite
|
Sign up to set email alerts
|

TRADD–TRAF2 and TRADD–FADD Interactions Define Two Distinct TNF Receptor 1 Signal Transduction Pathways

Abstract: Tumor necrosis factor (TNF) can induce apoptosis and activate NF-kappa B through signaling cascades emanating from TNF receptor 1 (TNFR1). TRADD is a TNFR1-associated signal transducer that is involved in activating both pathways. Here we show that TRADD directly interacts with TRAF2 and FADD, signal transducers that activate NF-kappa B and induce apoptosis, respectively. A TRAF2 mutant lacking its N-terminal RING finger domain is a dominant-negative inhibitor of TNF-mediated NF-kappa B activation, but does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
1,479
4
10

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,840 publications
(1,545 citation statements)
references
References 43 publications
52
1,479
4
10
Order By: Relevance
“…One of these molecules is TNF receptor associated factor 2 Figure 1 The mammalian stress-activated MAP kinase modules. The question marks indicate that direct evidence of these pathways remain to be established (TRAF2), which interacts directly with TNFR-2 (Rothe et al, 1994) but is recruited to TNFR-1 via its interaction with TNFR-1-associated death domain protein (TRADD; Hsu et al, 1995Hsu et al, , 1996b. To date, six members of the TRAF family have been identi®ed (Hu et al, 1994;Rothe et al, 1994;Cheng et al, 1995;Mosialos et al, 1995;Re gnier et al, 1995;Cao et al, 1996;Nakano et al, 1996).…”
Section: Tnf Receptor Associated Factors (Trafs)mentioning
confidence: 99%
See 1 more Smart Citation
“…One of these molecules is TNF receptor associated factor 2 Figure 1 The mammalian stress-activated MAP kinase modules. The question marks indicate that direct evidence of these pathways remain to be established (TRAF2), which interacts directly with TNFR-2 (Rothe et al, 1994) but is recruited to TNFR-1 via its interaction with TNFR-1-associated death domain protein (TRADD; Hsu et al, 1995Hsu et al, , 1996b. To date, six members of the TRAF family have been identi®ed (Hu et al, 1994;Rothe et al, 1994;Cheng et al, 1995;Mosialos et al, 1995;Re gnier et al, 1995;Cao et al, 1996;Nakano et al, 1996).…”
Section: Tnf Receptor Associated Factors (Trafs)mentioning
confidence: 99%
“…Overexpression studies have implicated TRAF2 in TNF-induced activation of JNK, p38 and NF-kB (Rothe et al, 1995a;Hsu et al, 1996b;Liu et al, 1996;Takeuchi et al, 1996;Natoli et al, 1997;Reinhard et al, 1997). NF-kB-inducing kinase (NIK; note: di erent from MAPKKKK NIK noted above) is a MAPKKK-related protein kinase that associates with TRAF2 and other members of the TRAF family and mediates activation of NF-kB through IKKs but does not activate JNK or p38 (Song et al, 1997).…”
Section: Tnf Receptor Associated Factors (Trafs)mentioning
confidence: 99%
“…IRAK then dissociates from the receptor complex and interacts with TRAF6, that is required for IL-1-induced NF-kB activation (Cao et al, 1996b). Two other TRAF (TNF-receptor associated factor) proteins, TRAF2 and TRAF5, have been implicated in NF-kB activation by the superfamily of TNF receptors (Aizawa et al, 1997; Duckett et al, 1997; Hsu et al, 1996aHsu et al, , 1997Ishida et al, 1996;Nakano et al, 1996;Rothe et al, 1995), indicating that IL-1 and TNF signaling converge at the level of TRAF molecules. The kinase cascade which is distal to TRAF, and is responsible for NF-kB activation, also has been elucidated.…”
Section: Egr-1 ±Modulation Of Lineage Speci®c DI Erentiation and Rolementioning
confidence: 99%
“…To activate NF-kB, TRADD interacts with serine/threonine kinase RIP and TRAF2, that are linked to the NIK/IkK cascade, and trigger the phosphorylation and degradation of IkB (Hsu et al, 1996a,b). On the other hand, to induce cell death, TRADD interacts with FADD, which in turn triggers the apoptotic caspase cascade (Boldin et al, 1996;Grimm et al, 1996;Hsu et al, 1996a;Muzio et al, 1996). Since in IL-1 signaling, MyD88 is responsible for recruiting IRAK, which interacts with TRAF6, it is the functional equivalent of TRADD in NF-kB activation by IL-1.…”
Section: Egr-1 ±Modulation Of Lineage Speci®c DI Erentiation and Rolementioning
confidence: 99%
“…To date, seven members of the TRAF family have been identified (TRAF1-7) (Arch et al, 1998;Baud et al, 1999;Bradley and Pober, 2001;Chung et al, 2002;Xu et al, 2004). TRAF2 mediates TNF-a-induced activation of AP-1 and NF-kB by directly associating with TNF-R2 (Rothe et al, 1994(Rothe et al, , 1995 and/or recruiting to TNF-R1 through interacting with TNF-R1-associated death domain protein (TRADD) (Hsu et al, 1995(Hsu et al, , 1996a. It has been well demonstrated that TRAF2 is crucial for downstream signaling events in response to TNF-a, and controls cell growth or death (Xia and Chen, 2005).…”
Section: Introductionmentioning
confidence: 99%